ATMOSPHERIC CARBON DIOXIDE CONCENTRATION AT SYOWA STATION (69°00′S, 39°35′E), ANTARCTICA (1985) - ムラヤマ, ハルタ; タナカ, マサユキ; ナカザワ, タカキヨ; カワグチ, サダオ; ヤマノウチ, タカシ; アオキ, シュウジ; シオバラ, マサタカ; MURAYAMA, Haruta; TANAKA, Masayuki; NAKAZAWA, Takakiyo; KAWAGUCHI, Sadao; YAMANOUCHI, Takashi; et al. (National Institute of Polar Research, 1987)
P(論文) Since 1984,continuous measurements of the atmospheric CO_2 concentration have been carried out at Syowa Station, Antarctica. Preliminary inspection of the data showed that; (1) a regular diurnal variation is not observable; (2) irregular variations are sometimes observed with an extremely small amplitude of 0.2ppmv at most; (3) a seasonal variation with the minimum concentration in mid-April and the maximum concentration in mid-October and peak-to-peak amplitude of about 1.2ppmv is detected; and (4) an annual mean value of CO_2 concentration is 342.6ppmv. The results obtained in 1985 are as follows : An annual mean value of CO_2 concentration is 343.8ppmv. The pattern of seasonal variation is almost the same as that of the previous year. But a secular increase trend of the CO_2 content is larger than 1984. departmental bulletin paper